BTS1-knockout Saccharomyces cerevisiae with broad-spectrum antimicrobial activity through lactic acid accumulation - Liu Cong; Yuan Zhou; Yu Zhang; Shanshan Mao; Chaoqun Chen; Liying Wang; Xiao Li; Zuo Zhang; Zuobin Zhu; Ying Li (Frontiers in Cellular and Infection Microbiology)
Bacterial infections pose significant threats to human health, and prudent antibiotic use remains a key strategy for disease treatment and control. However, a global escalation of drug resistance among pathogenic bacteria presents a formidable challenge. Probiotics have emerged as a promising approach to combating pathogenic bacterial infections. In this study, we investigated the antibacterial activity of BTS1-knockout (BTS1-KO) Saccharomyces cerevisiae. Our findings demonstrate its effective inhibition of pathogen growth as evidenced by Minimum inhibitory concentration (MIC) assays, growth curves, bacteriostatic spectrum analyses and co-culture experiments. Additionally, it significantly impedes Escherichia coli and Staphylococcus aureus biofilm formation. Moreover, BTS1-KO S. cerevisiae exhibits low haemolytic activity, acid resistance, resistance to high bile salt concentrations, high auto-aggregation capacity and high co-aggregation capacities with pathogenic bacteria. Moreover, infected larvae treated with BTS1-KO S. cerevisiae in Galleria mellonella-E. coli (in vivo) and G. mellonella-S. aureus (in vivo) infection models showed significantly prolonged survival times. Mechanistic investigations revealed that BTS1-KO S. cerevisiae primarily produced lactic acid via metabolism, thereby lowering the environmental pH and inhibiting pathogenic bacterial growth. In summary, our study underscores the probiotic potential of BTS1-KO S. cerevisiae, offering broad-spectrum antibacterial activity in vitro and in vivo with low toxicity. This highlights BTS1-KO S. cerevisiae as a promising probiotic candidate for clinical prevention and control of bacterial infection.